United States : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the United States. (IMF Staff Country Reports; Country Report ;, 2021)
The new administration's policies have put the U.S. economy on a strong footing. An effective vaccine rollout has put the number of new COVID-19 cases on a firmly downward path. At the same time, unprecedented fiscal support is quickly restoring the economy back to full employment and generating positive outward spillovers to the world economy. These efforts have not been costless: the path for public debt is far higher; the current account deficit has grown; and very accommodative financial conditions have led to increased corporate and nonbank leverage and rising valuations across a range of assets. The pandemic continues to weigh heavily on those at the lower end of the income distribution, exposing longstanding inequities in access to quality healthcare and education (many of which have an important gender and racial dimension).